Milne Fiord Oceanographic Mooring, 2011-2019 ... - Mueller, Derek; Bonneau, Jeremie; Hamilton, Andrew; Laval, Bernard (Canadian Cryospheric Information Network, 2021)
A series of temperature, conductivity-temperature and conductivity-temperature-depth loggers were placed on a rope suspended from the ~1-2 m thick perennial ice surface. The lower end of the rope was weighted down. Each logger was set to record continuously (at various intervals). Temperature loggers were Onset hobo temperature loggers, and RBR TR1050s, TR1060s and SoloTs. Note, Hobo temperature loggers were placed in the ice and on a vertical stake and measured air, snow or ice temperatures. CT/CTDs were Seabird SBE37, XT-420, XR-620. Instrument number and placement varied through time 15 to 27. Each year the mooring is retrieved. Each instrument program is then downloaded, batteries and desiccant are changed, time is synced and a new program is uploaded. At the top of the mooring, there is a cross of 2x4s that attaches to a 3 m PVC stake and 3 floats. That way, the mooring can be found and recovered if the ice breaks up (although this has not occurred yet). Visits to the mooring include: May 2011 (setup), ... : To determine the heat and salt budget of Milne Fiord along with changes in the depth of the epishelf lake which exists within the upper water column and deep water renewal events, a mooring was installed in the centre of Milne Fiord. This mooring has been maintained since May 2011 with only a few days of down time due to maintenance. A collection of temperature and conductivity data logged continuously from several depths in Milne Fiord. These data show how the fresh upper water column (also known as an epishelf lake) and the underlying sea water (to a depth of ~350 m) have changed over time in this Arctic fiord. ...